Analisis Manajemen Risiko dalam Pembiayaan Peer-to-Peer (P2P) di Sektor Fintech: Tantangan dan Strategi Mitigasi: Risk Management Analysis in Peer-to-Peer (P2P) Financing in the Fintech Sector: Challenges and Mitigation Strategies - Nurfuadi, Wika; Marliyah; Sugianto (Litera Academica Publishing, 2025)
The financial technology (fintech) industry in Indonesia, particularly Peer-to-Peer (P2P) lending, has experienced rapid growth in recent years, providing faster and easier access to capital for individuals and Micro, Small, and Medium Enterprises (MSMEs). While offering many advantages, such as efficiency and financial inclusion, P2P lending faces significant challenges in risk management, including credit, operational, and compliance risks. This research uses the literature study method to analyze the challenges faced by the P2P lending industry as well as the mitigation strategies that can be applied. The results show that low credit scoring quality, lack of historical borrower data, and cybersecurity threats are the main factors affecting risk. In addition, compliance with regulations set by the Financial Services Authority (OJK) is crucial to maintain the industry's reputation. This research recommends the application of advanced technology in credit assessment, diversification of loan portfolios, and strengthening of internal processes to mitigate risk. Thus, this research provides not only academic insights but also practical recommendations for industry players to improve risk management in P2P lending in Indonesia.